The Role of Identity Leadership in Enhancing Brand Alignment and Organizational Identity with Emphasis on Organizational Culture, Employee Commitment, and Internal Communication - Sharaf Tadavani, Mahdi; Cheraghsahar, Rasool (Management Strategies and Engineering Sciences, 2026)
The present study aimed to examine the role of identity leadership in strengthening the alignment between brand and organizational identity by considering the mediating roles of organizational culture, employee commitment, and internal communication. This study was conducted using a quantitative and applied approach with a survey design. The statistical population consisted of employees of banks in Fars Province, from which a sample of 400 participants was selected through random sampling. Data were collected using a 25-item questionnaire based on a five-point Likert scale. The reliability of the instrument was confirmed using Cronbach’s alpha, composite reliability, and average variance extracted (AVE). Data analysis was performed using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model was assessed in terms of reliability and convergent and discriminant validity, while the structural model was evaluated using path coefficients, coefficient of determination (R²), effect size (f²), and predictive relevance (Q²). The results indicated that identity leadership has a significant positive effect on organizational culture (β = 0.405, p < 0.01), employee commitment (β = 0.522, p < 0.01), and internal communication (β = 0.502, p < 0.01). Furthermore, organizational culture (β = 0.254, p < 0.01), employee commitment (β = 0.299, p < 0.01), and internal communication (β = 0.253, p < 0.01) were found to have significant positive effects on brand alignment and organizational identity. The model demonstrated acceptable explanatory power, with R² values of 0.164 for organizational culture, 0.273 for employee commitment, 0.252 for internal communication, and 0.341 for brand alignment and organizational identity. Positive Q² values confirmed the predictive relevance of the model. The findings suggest that identity leadership plays a critical role in fostering alignment between brand and organizational identity by enhancing organizational culture, strengthening employee commitment, and improving internal communication processes. These results highlight the importance of identity-based leadership as a strategic mechanism for achieving internal coherence and sustainable organizational performance.